CAKA: a novel cache‐aware K‐anycast routing scheme for publish/subscribe‐based information‐centric network. (27th April 2015) - Ren, Jing; Lu, Kejie; Tang, Fei; Wang, Jin; Wang, Jianping; Wang, Sheng; Liu, Shucheng
Summary: In the past few years, many publish/subscribe‐based information‐centric network (PS‐ICN) architectures have been proposed and investigated to efficiently deliver information from content publishers to subscribers. However, most existing studies on PS‐ICN have not considered how to utilize in‐network caches, which is a common but important feature in ICN. To address this issue, in this paper, we propose a novel cache‐aware K‐anycast routing scheme, namely, CAKA, that can significantly improve the performance of content delivery. Specifically, we choose PURSUIT, which is one of the most important PS‐ICN architectures, and leverage its bidirectional communication procedure to do the following: (1) enable multiple publishers to send probing messages to the same subscriber; and (2) allow the subscriber to retrieve content objects using K‐anycast routing and network coding . In this study, we extend the PURSUIT protocol to support cache‐aware K‐anycast routing and design the algorithms to choose multiple partially disjointed paths for probing, and to select paths for content retrieval. To evaluate the performance of the proposed scheme, we develop not only a simulation testbed, but also a prototype running in a realistic network environment. Our studies show that the proposed scheme can significantly reduce the average hops to retrieve content objects, with very small overheads. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper, we propose a novel cache‐aware K‐anycast routing scheme for publish/subscribe‐based information‐centric network, namely, CAKA, that can significantly improve the performance of content delivery. CAKA can do the following: (1) enable multiple publishers to send probing messages to the same subscriber; and (2) allow the subscriber to retrieve content objects using K‐anycast routing and network coding . To evaluate the performance of the proposed scheme, we develop not only a simulation testbed, but also a prototype running in a realistic network environment.